Effectiveness of Public Relations Media Campaigns in Enhancing Attention Economy Indicators among Asiacell’s Audience - Qayssar Jabbar Gatea, Dr. (lark, 2026)
This research aims to investigate the effectiveness of Public Relations media campaigns in enhancing the indicators of the attention economy among the audience of Asiacell and to identify the communicative and psychological variables most influential in achieving mental immersion for the recipient. The study was conducted on a field sample of (500) individuals from the company’s audience in Baghdad. The research falls within the scope of descriptive studies utilizing the survey method; the researcher employed a questionnaire and two standardized scales to collect and analyze the data. The results concluded a statistically significant correlation between campaign quality and the level of realized attention. It was found that social and humanitarian content represents the strongest catalyst for mental absorption, significantly outperforming service and entertainment content. Statistical analyses revealed—contrary to common hypotheses regarding the dominance of social media—the superiority of the company’s mobile application as a communicative environment capable of attracting focused attention compared to open platforms. The results demonstrated a substantial variation attributed to the cognitive level; individuals with higher educational attainment and interactive motives such as participation and loyalty recorded the highest levels of attention. This demonstrates that the success of the attention economy relies not on fleeting view intensity but on emotional value and cognitive engagement that transform the audience from passive consumers into partners immersed in the communicative message